Development and validation of a fast and optimized screening method for enhanced production of secondary metabolites using the marine Scopulariopsis brevicaulis strain LF580 producing anti-cancer active scopularide A and B. - Annemarie Kramer (Public Library of Science (PLoS), 2014)
Natural compounds from marine fungi are an excellent source for the discovery and development of new drug leads. The distinct activity profiles of the two cyclodepsipeptides scopularide A and B against cancer cell lines set their marine producer strain Scopulariopsis brevicaulis LF580 into the focus of the EU project MARINE FUNGI. One of the main goals was the development of a sustainable biotechnological production process for these compounds. The secondary metabolite production of strain LF580 was optimized by random mutagenesis employing UV radiation. For a fast and reliable detection of the intracellular secondary metabolite production level, a miniaturized bioactivity-independent screening method was developed, as the random mutagenesis yielded a large number of mutants to be analysed quantitatively and none of the existing hyphenated bioassay-dependent screening systems could be applied. The method includes decreased cultivation volume, a fast extraction procedure as well as an optimized LC-MS analysis. We show that deviation could be specifically reduced at each step of the process: The measuring deviation during the analysis could be minimized to 5% and technical deviation occurring in the downstream part to 10-15%. Biological variation during the cultivation process still has the major influence on the overall variation. However, the approach led to a 10-fold reduction of time and similar effects on costs and effort compared to standard reference screening methods. The method was applied to screen the UV-mutants library of Scopulariopsis brevicaulis LF580. For validation purposes, the occurring variations in the miniaturized scale were compared to those in the classical Erlenmeyer flask scale. This proof of concept was performed using the wild type strain and 23 randomly selected mutant strains. One specific mutant strain with an enhanced production behavior could be obtained.